Satellite study of western disturbances - AGNIHOTRI, C. L.; SINGH, M. S. (MAUSAM, 1982)
Study of western disturbances approaching NW India and neighbourhood during winter period (November-March) has been made with the help of satellite cloud imageries of 10 years. It has been shown that three distinct types of cloud masses could be detected, of which the most common ones are the overcast shapeless cloud masses forming in the belt 25 deg.-35 deg. N, 40 deg.- 50 deg. E and approaching NW India moving eastward. They are associated with the secondaries of the extra-tropical depressions moving NE'ward from the Mediterranean. These secondary systems generally form in the Persian Gulf-Black Sea region and move ENE/E'wards over an area (Middle East) of generally sparse data, thus making it difficult sometimes to follow them on synoptic charts properly. These are mostly shallow systems not extending above 700 mb. The study of cloud masses associated with them shows that they remain well organised and could be followed systematically. They reach the country in about 2 days' time from the Persian Gulf area and sometimes strengthen when over NW India. For the prediction of such systems, therefore, satellite cloud photographs seem to be of great help.